Pengaruh Umur Usaha, Pengetahuan Akuntansi, Pendapatan Usaha terhadap Penggunaan Informasi Akuntansi pada UMKM “Pedagang Kaki Lima” di Kota Kendal - Dewi Sekar Sari; Luluk Muhimatul Ifada (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The development of MSMEs (Micro, Small, and Medium Enterprises) is very important to be paid attention to by the government and the community because it plays a significant role in driving the national economy. As MSMEs grow and develop, they create new jobs that directly help reduce unemployment rates and improve people's welfare. In addition, the success of MSMEs can also strengthen the local economic structure through the turnover of domestic products and community empowerment. One of the important aspects in MSME management is the use of adequate accounting information in order to make rational and measurable business decisions. The type of research used is quantitative research with an explanatory research approach. The sampling technique used the Slovin formula, with a sample of 93 respondents from MSMEs, especially street vendors in Kendal City. The data collection instrument was in the form of a questionnaire which was analyzed using the multiple linear regression method. The results of the study show that the age of the business has a positive and significant effect on the use of accounting information. The longer a business runs, the higher the tendency of business actors to utilize accounting information in managing their business. In addition, accounting knowledge also has a positive and significant influence on the use of accounting information, showing that a basic understanding of accounting is an important factor in financial decision-making. Likewise, business income has been proven to have a positive and significant influence on the use of accounting information. This study concludes that these three variables – business age, accounting knowledge, and business income – together encourage the increase in accounting literacy in the MSME sector. Therefore, training and socialization related to simple accounting need to be improved to strengthen the sustainability of small businesses in the long term.